Assessing Estonia’s viticultural potential based on the compositional analysis of sugars and acid compositional analysis of wine grape cultivars - Reelika Rätsep; Mariana Maante-Kuljus; Kadri Karp; Priit Põldma; Angela Koort; Leila Mainla; Ulvi Moor (Agricultural and Food Science)
The primary objective of this study was to assess Estonia’s potential for viticulture through the calculation of the Heliothermal Index and analysis of its 20-year dynamics. The secondary objective was to determine the variability in grape sugars and acids composition depending on vintage (2023, 2024) and cultivar characteristics in ‘Solaris’, ‘Regent’, ‘Leon Millot’, ‘Cabernet Cortis’, ‘Marquette’, ‘Hasansky Sladky’, ‘Zilga’, and ‘Rondo’. Over the twenty years, the Heliothermal Index ranged from 872 to 1622, showing a warming trend with implications for viticultural potential. Fructose content in grapes ranged from 72 to 98 g l⁻¹, with ‘Marquette’ having the highest and ‘Zilga’ the lowest. Glucose content was lowest in ‘Zilga’ (64 g l⁻¹) and highest in ‘Marquette’ (98 g l⁻¹). ‘Zilga’ had the highest tartaric acid content (5.9 g l⁻¹), while ‘Leon Millot’ (3.5 g l⁻¹) and ‘Regent’ (3.7 g l-1) had the lowest. ‘Hasansky Sladky’ had the highest malic acid content (5.5 g l⁻¹), while ‘Regent’ (2.1 g l⁻¹) and ‘Solaris’ (2.5 g l⁻¹) had the lowest. The study confirmed that the tested cultivars are suitable for producing dry wine in Estonia, which belongs to the EU viticulture zone A.